A laboratory study on the hygroscopic behavior of H2C2O4-containing mixed particles. (1st March 2019) - Ma, Qingxin; Liu, Chang; Ma, Jinzhu; Chu, Biwu; He, Hong
Abstract: The climatic effect of atmospheric particles is greatly dependent on their hygroscopicity and chemical composition. Although the hygroscopic behavior of individual components of aerosol has been widely studied, the effect of coexisting species on the hygroscopic behavior of mixed constituents is still not clear. In this study, we used Raman spectroscopy to investigate how particles with different hygroscopic behaviors affect each other when they are combined together in mixtures. The effect of coexisting hygroscopic components, e.g. NaCl, NH4 NO3, and (NH4 )2 SO4, on the hygroscopic behavior of externally mixed H2 C2 O4 /CaCO3 was studied. We found that coexisting NH4 NO3 can promote the conversion of H2 C2 O4 /CaCO3 to CaC2 O4 ·H2 O in the humidifying process by providing a deliquesced solution to dissolve H + in the oxalic acid matrix. Moreover, competition and blocking effects existed in the case of coexisting (NH4 )2 SO4 . Reactions between (NH4 )2 SO4 and CaCO3 led to the formation of CaSO4 ·2H2 O and (NH4 )2 C2 O4 instead of CaC2 O4 . NaCl reacted with H2 C2 O4 in solution to form Na2 C2 O4 . These results suggested that synergistic effects between coexisting components in mixed particles during the humidifying-dehumidifying process may change their chemical composition, mixing state, and hygroscopicity. In addition, chemical reactions should be considered in future studies on the hygroscopic behavior of mixed particles. Graphical abstract: Highlights: Hygroscopic behaviors of oxalic acid containing mixed particles were studied. Reactions occurred during the humidifying process of mixed particles. Coexisting hygroscopic components promote the reaction between H2 C2 O4 and CaCO3 . The final composition depends on the hygroscopicity of the products.